Housing habits and their implications for life-cycle consumption and investment - Holger Kraft; Claus Munk; Sebastian Wagner (Goethe University Frankfurt, SAFE - Sustainable Architecture for Finance in Europe, 2015)
We solve a rich life-cycle model of household decisions involving consumption of perishable goods and housing services, habit formation for housing consumption, stochastic labor income, stochastic house prices, home renting and owning, stock investments, and portfolio constraints. In line with empirical observations, the optimal decisions involve (i) stock investments that are low or zero for many young agents and then gradually increasing over life, (ii) an age- and wealth-dependent housing expenditure share, (iii) non-housing consumption being significantly more sensitive to wealth and income shocks than housing consumption, and (iv) non-housing consumption being humpshaped over life.
Keywords: G10; D14; D91; E21; R21; 330; Habit formation; life-cycle household decisions; housing expenditureshare; consumption hump; stock market participation; human capital